An Assessment of China’s Digital Trade Development and Influencing Factors - Hu, Yue; Zhou, Han Qian; Yan, Bin; Zou, Zhou; Li, Yu’an (Frontiers in Psychology, 2022)
This paper constructs a comprehensive evaluation system of digital trade development level from information network facilities, information technology level, digital industrialization level and industry digitalization level by using Entropy-TOPSIS Model to measure China's Digital Trade Development Level. The results indicate that China's digital trade development is generally on the rise from 2010 to 2019. The main factors which affect the development level of digital trade in China were further explored based on principal component analysis. The empirical study finds that Internet development, residents' income, industrial structure, payment convenience level, fixed asset investment, online transaction scale and economic development level contribute to the development of digital trade in China. Among them, the most significant impact is on the level of payment convenience. The degree of government intervention and foreign trade dependence have a negative effect on the development of digital trade.